Evaluation of adalimumab effects on left ventricle performance by echocardiography indexes among patients with immunosuppressant refractory ulcerative colitis - Hatamnejad, Mohammad Reza; Karvandi, Mersedeh; Jodatfar, Fateme; Ebrahimi, Nastaran; Shojaeian, Fatemeh; Baradaran Ghavami, Shaghayegh; Balaii, Hedieh; Moeeni, Mahdi; Rajabnia, Mohsen; Shahrokh, Shabnam; Asadzadeh Aghdaei, Hamid (Frontiers in Medicine, 2023)
Background and Aims: Inflammatory bases lead to a simultaneous flourishing of cardiovascular complications with IBD. As a released cytokine, tumor necrosis factor-α (TNF-α) can either disrupt or preserve cardiovascular performance. Because of this controversy, this study aimed to appraise the short-term anti-TNF (adalimumab) relics on cardiac function by gauging the echocardiography indexes in immunosuppressant refractory ulcerative colitis (UC) patients. Methods: All cases with a definite diagnosis of UC were included based on providing written informed consent and owning the severe form of active disease (Mayo score ≥7), which did not dampen with immunosuppressant. Patients were excluded in the case of previous cardiac ailments/risk factors and prior related surgical or pharmaceutical intervention. Transthoracic echocardiography was carried out before and three months after biological regimen allocation and indexes [ejection fraction (EF), left ventricular end-diastolic/systolic volume (LVEDV and LVESV), and global longitudinal strain (GLS) in standard parasternal short axis from mid-ventricular level, two-, three-, and four-chamber apical long axes] alteration were compared via statistical analyses. Results: The study consisted of 13(65%) men and 7(35%) women, with a mean age of 36.54 ± 11.3 years. Participants mainly possessed Montreal class I (45%) and an average of 3.25 years of disease duration. The intervention significantly controlled inflammation (endoscopic Mayo score (P = 0.001), partial Mayo score (P = 0.001), and C-reactive protein (P = 0.001). Endoscopic and clinical remission, were obtained in 7(35%) and 9(45%) patients, respectively; however, no significant discrepancy related to the LVEDV (P = 0.86), LVESV (P-value = 0.25), EF (P-value = 0.06), and GLS in standard parasternal short axis (P=0.73), long-axis [apical 2-chamber (P-value = 0.61), apical 3-chamber (P-value = 0.15), and apical 4-chamber (P-value = 0.19)] was seen before and after the intervention. Furthermore, no statistically significant correlation between disease activity and cardiac function was found, neither before nor after adalimumab administration. Conclusion: The present perusal found no deterioration in left ventricular function indexes with ADA intervention among IBD patients without cardiac ailment. Thus, prescribing the Anti-TNF to alleviate the inflammation can be carried out with less concern about cardiac consequences and considering other adverse traces in the target group.